Impact of technological progress on economic growth in developed countries. Accounting for model uncertainty and reverse causality (Economic and Political Thought, 2020)
The aim of this paper is to analyse the relationship between thedeterminants of technological innovation and economic growth. Moreover,it is aimed at examining whether expenditures on R&D variable hasa stronger impact on economic growth, comparing to other determinants oftechnological development. The primary reason to choose the topic is that weare living in a century of notable technological change and investigating therelationship between technology progress and economic development is theway to find new methods of accelerating economic growth. The literature onthis topic is extremely rich and many authors claim that the main driver oflong-term economic growth is technological innovation. Furthermore, overthe previous fifty years, a key financial finding has been that technologicalprogress is crucial to long-term economic growth. This paper uses panel datafor 19 developed countries over the period of 45 years (1973–2017) to examinethe effect of such variables as expenditures on R&D, panel applications andR&D personnel on GDP per capita. The paper uses panel Bayesian ModelAveraging under weak exogeneity. The results obtained show that all threeindicators of technological innovation have a positive impact on per capitaGDP and that expenditures on R&D have the strongest effect on economicgrowth.
Keywords: innovation, technology, economic growth, R&D, patent